Sex-related differences in acute coronary syndrome: insights from an observational study in a Yemeni cohort - Al-Assadi, Muammar Yahiya; Aljaber, Nouradden Noman; Al-Habeet, Abdulhafeedh; Al Nono, Osama; Al-Motarreb, Ahmed (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute coronary syndrome (ACS) presents with significant sex-related differences globally, yet research within Yemen remains limited. This study investigates these differences in the clinical presentation, management, and outcomes of Yemeni patients with ACS.MethodsA retrospective cohort study was conducted at six tertiary care centers, including 1,743 patients (1,379 men and 364 women) hospitalized with ACS between January 2020 and December 2023.ResultsOn average, women were generally older than men (59.4 ± 11.7 vs. 57.9 ± 12.7 years, P = 0.031) and more frequently diagnosed with non-ST elevation ACS (35.2% vs. 28.9%, P = 0.021). Women also exhibited higher rates of traditional cardiovascular risk factors, including diabetes mellitus (31.9% vs. 20.8%, P < 0.001) and hypertension (44.5% vs. 32.0%, P < 0.001), but had a lower prevalence of atrial fibrillation (0.8% vs. 2.5%, P = 0.033) and less likely to engage in ACS lifestyle risk behaviors like smoking (31.0% vs. 83.0%, P < 0.001) and khat chewing (53.3% vs. 83.7%, P < 0.001). Women were less likely to receive coronary angiography (47.5% vs. 61.3%, P < 0.001) or percutaneous coronary intervention (33.8% vs. 46.6%, P < 0.001) and were discharged with fewer guideline-recommended therapies for secondary prevention. Women experienced worse in-hospital outcomes, with a significantly higher in-hospital mortality rate (12.6% vs. 7.6%, P = 0.002), especially among those with ST-elevation myocardial infarction (STEMI), which remained significant even after adjustment for all clinical confounding factors (adjusted odds ratio, 1.80; 95% CI, 1.16–2.78, P = 0.008). However, the one-year mortality rate showed no significant difference between genders.ConclusionYemeni women with ACS experience disparities in treatment and worse in-hospital outcomes, especially in STEMI cases. Addressing gender biases through public health education, healthcare provider training, and infrastructure improvements is essential to improving outcomes.